Modeling and analysis of wireless inductive power transfer link - Nataraj, Chandrasekharan (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Significant advancements in the electronics industry and the use of low power portable devices in the consumer electronic applications have motivated researchers to develop different variety of wireless solutions. Most of these portable devices are battery-operated, requiring periodical recharging. This dissertation presents the study of different coil geometries for developing low-power wireless inductive link as a solution for battery-less gadgets. The developed wireless inductive link also addresses the power loss limitations to enhance power transfer efficiency. Different coil geometries used as both transmitter and receiver coils, are investigated through mathematical modeling and using COMSOL (Finite Element Method) simulation. Achieving better power transfer efficiency over a relatively wider distance between coils is the prime objective in most of the wireless power transfer systems, but it often suffers from power loss in the coil vicinity. One of the viable methods will be to reduce the power loss by field beaming for increased intensity. With this aim, three multi-turn coils of solenoid, spiral and conical are designed and simulated using COMSOL platform to determine the field strength. It is observed that the conical coil produces highest self-inductance of 8.63 µH with a field strength of 1.542 Wb at the switching frequency of 13.56 MHz. Another group of single turn coils based on spiral, square, and rectangular geometry are designed and simulated using HFSS software at a switching frequency of 220 kHz. The performance of these single and multi-turn coils are evaluated to show that the conical and spiral are best suited as transmitter and receiver coils. In addition, the LCC topology with class-E power amplifier design is demonstrated with the coupling factor k = 0.1 using ADS software to reduce the power loss comparatively over an increased coil separation distance. Subsequently, two lab-scale wireless inductive links are constructed for experimental measurements and evaluation. Two inductive links of conical-to-spiral and spiral-to-spiral are demonstrated to explore the effect of coil misalignment and coil separation distance on the efficiency. The system is tested under 13.56 MHz switching frequency and a resistive load of 4 Ω connected at the receiver end. The coil separation distance range of 0 to 50 cm is used for voltage measurements. The outcomes achieved proves that conical-to-spiral inductive link produces better power transfer efficiency of 63%, than the widely used spiral-to-spiral inductive link efficiency of 48%. Finally, it is concluded that the developed conical coil based inductive link exhibits exceptionally better performance in terms of power transfer efficiency and coil separation distance. The results of this work find application in powering low-power portable consumer gadgets or devices buried or in location sites inaccessible to wiring means of power transfer.